2022
DOI: 10.3390/app12041869
|View full text |Cite
|
Sign up to set email alerts
|

Impact Properties of Novel Natural Fibre Metal Laminated Composite Materials

Abstract: Fibre metal laminates (FMLs) are lightweight structures with high structural performance and are suitable for many industrial applications. This work describes the impact behaviour of novel sisal fibre-reinforced aluminium laminates (SiRAL) and their dependence upon the orientations of the fibres, the composite core used and the surface treatment of the metal skins. A cold-pressing technique is used to produce SiRALs in six configurations. The FMLs here also have treated or untreated aluminium skins (2024 T3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Autoclave, out‐of‐autoclave, and hot press molding compression techniques can all be applied to produce natural fiber‐based FMLs. Vieira et al 149 prepared the sisal fiber‐reinforced epoxy metal laminates using the hand lay‐up method, followed by cold pressing at 1500 Pa. Yaghoobi et al 150 used vacuum‐assisted resin infusion to produce basalt fiber‐reinforced liquid methyl methacrylate metal laminates. Ng et al 151 employed hot press molding compression technique to manufacture pineapple leaf/glass fiber‐reinforced polypropylene hybrid FMLs.…”
Section: Manufacturing Technique Of Natural Fiber‐based Fmlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoclave, out‐of‐autoclave, and hot press molding compression techniques can all be applied to produce natural fiber‐based FMLs. Vieira et al 149 prepared the sisal fiber‐reinforced epoxy metal laminates using the hand lay‐up method, followed by cold pressing at 1500 Pa. Yaghoobi et al 150 used vacuum‐assisted resin infusion to produce basalt fiber‐reinforced liquid methyl methacrylate metal laminates. Ng et al 151 employed hot press molding compression technique to manufacture pineapple leaf/glass fiber‐reinforced polypropylene hybrid FMLs.…”
Section: Manufacturing Technique Of Natural Fiber‐based Fmlsmentioning
confidence: 99%
“…When the density was considered, woven sisal fiber‐reinforced FMLs still showed the greatest specific mechanical properties. Vieira et al 149 made a further investigation on the impact properties of untreated and mechanical surface‐treated sisal fiber‐reinforced epoxy metal laminates with varying fiber orientations. They reported that fiber orientation at an off‐axis angle and mechanical surface treatment provided FMLs with the highest energy absorption and deflection properties.…”
Section: Natural Fiber‐based Fmlsmentioning
confidence: 99%
“…The characteristics of FMLs are excellent stiffness and strength in relation to density, high fatigue strength (Alderiesten, 2019), resistance to dynamic loads (Li et al, 2023;Vieira et al, 2022), compression (Kalfountzos et al, 2022) and stretching (Sun et al, 2023). In addition, they are characterized by high resistance to environmental conditions including corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Impact resistance of composite materials is one of the most important and critical issues [ 34 ]. Therefore, in this study, the low-velocity impact (drop weight impact) response of glass fiber reinforced 3D integrated woven spacer sandwich composites have been examined experimentally.…”
Section: Introductionmentioning
confidence: 99%